Magazines and the making of America : modernization, community, and print culture, 1741-1860 - Haveman, Heather A. (Princeton studies in cultural sociology., 2015)
From the colonial era to the onset of the Civil War, Magazines and the Making of America looks at how magazines and the individuals, organizations, and circumstances they connected ushered America into the modern age. How did a magazine industry emerge in the United States, where there were once only amateur authors, clumsy technologies for production and distribution, and sparse reader demand? What legitimated magazines as they competed with other media, such as newspapers, books, and letters? And what role did magazines play in the integration or division of American society?